LAPORAN AUDITOR, UKURAN AUDITOR DAN RELEVANSI NILAI INFORMASI AKUNTANSI (Studi Empiris pada Perusahaan non-Keuangan yang Terdaftar di BEI Tahun 2011-2020) - Winda Pratiwi; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2022)
This study aims to examine the effect of auditor reports and audit firm size on the value of the relevance of accounting information from companies listed on the Indonesia Stock Exchange in 2011-2020. This study uses the dependent variable (market value), independent variables (Book Value per Share and Earnings per Share), moderating variables (Audit Opinion and Audit Firm Size), and control variables (Size and Loss).The population in this study are non-financial companies listed on the Indonesia Stock Exchange in 2011-2020. By using purposive sampling in sample selection, 380 research samples were obtained for 10 consecutive years (2011-2020). The hypothesis of this research using multiple regression analysis method.The findings of this study reveal that audit opinion and auditor firm size are positively and significantly correlated with two indicators of value relevance of accounting information that affect the company's market value, namely Book Value per Share and Earnings per Share